Riesgo de anemia en adultos de ambos sexos de la asociación de exalumnos Ramiristas del distrito de moche, octubre del 2016 - Sanchez Rodríguez, Samuel Orlando (2018)
The objective of this study is to determine the risk of anemia in adults of both sexes of the Ramiristas ex student association, October 2016; previous informed consent, the samples were taken by performing the biochemical determinations of hemoglobin by means of the Cyanometahemoglobin method, hematocrit by the microhematocrate method - microcentrifugation and serum iron by the direct colorimetric method. A total of 50 volunteer participants, 44 women (88%) and 6 men (12%). the level of hemoglobin in 32 people (64%) has normal values (Women 12-16 g / dL, Men 13-18 g / dL), and 18 residents (36%) with diminished values (Women <12 g / dL; Men <13 g / dL), hematocrit was found that 7 people (14%) with decreased values (<37 in women and <40 in men), 43 people (86%) presented normal values of hematocrit (37 - 47% in women and 40 - 54% in men), serum iron was found that 7 people (14%) have decreased levels (Women <50 ug / dl, Men <65 ug / dl) and 43 people (86%) have normal values ( Women 50 to 170 ug / dl, Men 65 to 175 ug / dl). For the risk of anemia, a test was applied to collect data such as age, body mass index, eating habits, diseases, etc. Finding that 74% of people are at low risk of suffering from anemia. 14% slightly elevated risk, 8% moderate risk, 2% high risk, and no person presents very high risk, likewise, there is no significant relationship between gender and the risk of anemia (p = 0.23), which is greater than 5%.